Facile Synthesis of β-Bromostyrenes by Direct Bromination of Styrenes with N-Bromosuccinimide and Sodium Persulfate - Jing, Yi; Gao, Yan; Zhao, Qianyi; Chen, Xuenian; Ma, Yan-Na (Synlett, 2020)
A new, direct, efficient, and transition-metal-free method is reported for the synthesis of β-bromostyrenes from styrenes by using N-bromosuccinimide as the brominating reagent and sodium persulfate (Na2S2O8) as the oxidant. This convenient and concise reaction is practical, operationally simple, and can be adapted for large-scale syntheses.
Keywords: bromination; styrenes; bromosuccinimide; green chemistry; sodium persulfate; bromostyrenes